The Reconstruction of society ındigenous science into scientific knowledge in the production process of palm sugar - Sumarnı, Woro; Sudarmin; Wiyanto; Supartono (Journal of Turkish Science Education, 2016)
This research was aimed to reconstruct society indigenous science into scientific knowledge in the production process of palm sugar that was conducted on the people of Lendoh Hamlet, Leban Village, Boja Subdistrict, Kendal Regency, Central Java, Indonesia. The outform of this research were numbers of scientific knowledge from the result of society indigenous science reconstruction that was based on Javanese Culture about the production of palm sugar. The expected benefit of this research was to be the contextual educational resource for teacher of science on the school. The method of this research was qualitative descriptive through visceral interview, direct observation and document study about traditional production of palm sugar, and also scientific literature about nira and palm sugar. The research focus was the tradition of palm sugar production especially on knowledge of traditional sugar craftsman related to the raw materials palm nira and palm sugar production process. The obtained data were analyzed, verified, and constructed into scientific knowledge and were interpreted to get meaningful information. The conclusion was that there were five ten indigenous science from the palm sugar production which could be reconstructed into scientific knowledge.